2015
DOI: 10.1002/cbm.1966
|View full text |Cite
|
Sign up to set email alerts
|

Personal recovery within forensic settings – Systematic review and meta‐synthesis of qualitative methods studies

Abstract: The themes identified provide for theoretically informed and testable developments in care that could enhance the quality of recovery and rehabilitation for offender patients through explicitly enhancing personal sense of safety, understanding the patient's sense of personal identity and their social networks and transitioning between institutional and community support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 25 publications
9
72
0
Order By: Relevance
“…These themes overlap and extend the findings of Shepherd et al (), who synthesised five of the same studies included in the Clarke et al () review. They identified three major themes as supporting the recovery process: hope and social networks, a personal sense of safety and security (provided by the physical environment, relationships with care providers, or both), and identity work (making sense of past experiences, understanding the role of disorder, and constructing a sense of self).…”
Section: Patient Experiences Of Secure Recoverysupporting
confidence: 70%
See 2 more Smart Citations
“…These themes overlap and extend the findings of Shepherd et al (), who synthesised five of the same studies included in the Clarke et al () review. They identified three major themes as supporting the recovery process: hope and social networks, a personal sense of safety and security (provided by the physical environment, relationships with care providers, or both), and identity work (making sense of past experiences, understanding the role of disorder, and constructing a sense of self).…”
Section: Patient Experiences Of Secure Recoverysupporting
confidence: 70%
“…Several studies have now identified key principles of recovery as expressed by forensic mental health service users (e.g., Drennan & Aldred, ; Drennan & Woolridge, ; Livingston, ; Livingston, Nijdam‐Jones, Lapsley, Calderwood, & Brink, ; Nijdam‐Jones, Livingston, Verdun‐Jones, & Brink, ), including two reviews (Clarke, Lumbard, Sambrook, & Kerr, ; Shepherd, Doyle, Sanders, & Shaw, ). Clarke et al () conducted a systematic review and narrative synthesis of the 11 qualitative studies on offender‐patient perceptions of personal recovery, identifying six super‐ordinate themes: connectedness, sense of self, coming to terms with the past, freedom, hope, health, and intervention.…”
Section: Patient Experiences Of Secure Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Livesley (2005) described five phases for helping people with personality disorders; Laura's current treatment fits into the second step (containment) for which the aims are to stabilize emotions, manage distress and provide structure whilst starting to build therapeutic relationships. Additionally, Shepherd et al (2016) explain that providing safety and security is important for future recovery. Ultimately it was hoped that Laura could begin to develop an understanding of her emotions and resulting behaviours and engage in low-stimulus activities to occupy her time and reduce boredom (Green & Robinson, 2005), which Laura has said can trigger agitation.…”
Section: Precipitating Factors -Events or Circumstances That May Havementioning
confidence: 99%
“…The need for research within this area has been previously highlighted . More recently, Clarke et al and Shepherd et al have answered this call by publishing meta synthesis of 11 and 5 qualitative studies, respectively, exploring the subjective recovery of forensic mental health patients. Recovery has been most commonly explored qualitatively using a cross‐sectional design.…”
Section: Introductionmentioning
confidence: 99%